Action Observation With Dual Task for Improving Cognitive Abilities in Parkinson’s Disease: A Pilot Study - Caligiore, Daniele; Mustile, Magda; Fineschi, Alissa; Romano, Laura; Piras, Fabrizio; Assogna, Francesca; Pontieri, Francesco E.; Spalletta, Gianfranco; Baldassarre, Gianluca (Frontiers in Systems Neuroscience, 2019)
Action observation therapy has been recently proposed as a new rehabilitation approach for treatment of motor deficits in Parkinson’s disease. To date, this approach has never been used to deal with cognitive deficits (e.g., deficits in working memory, attention), which are impairments that are increasingly recognized in Parkinsonian patients. Typically, patients affected by these dysfunctions have difficulty filtering out irrelevant information and tend to lose track of the task goal. In this paper, we propose that action observation therapy may also be used to improve cognitive abilities of Parkinsonian patients if it is used within a dual task framework. We articulate our hypothesis by pivoting on recent findings and on preliminary results that were obtained through a pilot study that was designed to test the efficacy of a long-term rehabilitation program that, for the first time, uses action observation therapy within a dual task framework for treating cognitive deficits in patients with Parkinson’s disease. Ten Parkinson’s disease patients underwent a 45-minute treatment that consisted in watching a video of an actor performing a daily-life activity and then executing it while performing distractive tasks (action observation therapy with dual task). The treatment was repeated three times per week for a total of four weeks. Patients’ cognitive/motor features were evaluated through standard tests four times: one month before treatment, the first and the last day of treatment and one month after treatment. The results show that this approach may provide relevant improvements in cognitive aspects related to working memory (verbal and visuospatial memory) and attention. We discuss these results by pivoting on literature on action observation and recent literature demonstrating that the dual task method can be used to stimulate cognition and concentration. In particular, we propose that using action observation therapy together with a dual task may train the brain systems supporting executive functions through two mechanisms: (i) stimulation of goal setting within the mirror neuron system through action observation; (ii) working memory and persistent goal maintenance through dual task stimuli.